Concept of HBV and HCV as a risk factor and prevention of viral hepatitis-related hepatocellular carcinoma - Athraa Falah Alshimerry; Rawaa Ghalib Farhood (Medical Journal of Babylon, 2023)
Hepatocellular carcinoma (HCC) represents one of the most common cancers worldwide, and it is a very important reason for cancer-related death. Infection with hepatitis B virus (HBV) and hepatitis C virus (HCV) is considered the major leading cause of HCC. The pathophysiology of HB and HC viral-related HCC includes chronic inflammation, deorganization of cell signaling pathways, and oxidative stress. Contrary to HCV, HBV is oncogenic by itself, due to its integration into the DNA of cell. Six months of ultrasound monitoring is recommended for high-risk patients. Using antiviral drugs to manage viral hepatitis decreases the risk of evolution and reoccurrence of HCC. Also, effective preventive measures are very important in decreasing the risk of HCC. The prevention involves primary prevention which is based on HBV vaccination, treatment of acute infection, and eliminating the route of transmission, while secondary prevention is based on using antiviral drugs against HBV and HCV infection to prevent the progress of disease into carcinoma. However, tertiary prevention involves treating the carcinoma to prevent the reoccurrence of the cancer.